Arquitectura na (re) construção da paisagem: Natureza, Lugar, Cultura, Memória e Projecto em dois casos de estudo.
The landscape is the result of a long construction. The man tryed to understand nature, but as he could not understand it and was afraid of natural world's chaos, organised it and ordered it. From this transformation throughout history, related with its circumstances and with man's needs and activities, appeared representive landscapes of human's culture and identity. Because this construction follows man's evolution and ideologies some landscapes were changed and replaced until the present day. To project for the current landscape requires a detailed analysis. The new architecture must engage with the multiple elements that conciliate the landscape: nature, place, culture and memory. An architectural project to the landscape looks for: a relationship with the "whole" and with the proximity; a continuous construction with space and time; integration in the atmosphere; the meaning of the work in context, that is, the relationship with that landscape's man. This architecture is thought in consideration with the elements of historical value, but does not deny the inovation of new architecture in the long history of the landscape. The rural landscape and the urban landscape, despite opposites, require the same principles of analysis. In unique places, like the rural landscape of Pico island or the historic center of Porto, the construction of a project recovered a lost memory and continued a cycle of the landscape.